The Effect of Working Capital, Production Costs, and Selling Prices on Rice Farmers' Income in Kemuning Farmer Group, Pematang Ganjang Village, Sei Rampah District - Agus Suasana; Saputra, Hendra (LPPM STIE EKA PRASETYA, 2025)
This study aims to determine the direct and indirect effects of working capital, production costs, and selling prices on the income of rice farmers in the Kemuning Farmers Group, Pematang Ganjang Village, Sei Rampah District. This research method uses a quantitative approach with a sampling technique of total sampling with a sample size of 49 members of the Kemuning Farmers Group. The data used in this study are primary data which are the results of questionnaires, as well as secondary data sourced from the Kemuning Farmers Group, Pematang Ganjang Village and other documents. Data analysis techniques used in this study are validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, hypothesis tests with regression analysis, correlation and determination coefficient tests, t-tests, path analysis, and sobel tests with the help of SPSS software. The results of the study indicate that working capital has a significant positive effect on selling price, production costs have a significant positive effect on selling price, working capital has a significant positive effect on income, production costs have a significant positive effect on income, selling price has a significant positive effect on income, working capital on income through selling price has an insignificant effect or in other words that the relationship or test effect is not strong enough, production costs on income through selling price have a significant effect in other words the selling price variable can mediate the effect of production costs on income.